Circular economy applied to architecture illusion or reality - Climent, Andreu (Universidad de Lima. Carrera de Arquitectura, 2021)
DOI: https://doi.org/10.26439/limaq2021.n007.5178 Even though current society seems to be slowly moving toward a more sustainable world, it still depends on the increasingly limited supply of natural resources. Therefore, the consumerist model―governed by the take–make–waste triad―keeps dominating the global political– economic scenario. In this situation of imbalance between the consumption of natural resources and the production of waste, a new economic model of cyclical shape called “circular economy” has been developed in the last few years. Such model aims at optimizing each material’s lifetime by reducing the environmental impact generated by its production process. This work examines the applicability of the circular model to the architectural field through the analysis of real experiences and proposes its implementation as a reliable constructive method. Tomorrow’s architecture is already building its foundations.